New taxonomic considerations in the spitting spider family Scytodidae (Arachnida: Araneae) - Zamani, Alireza; Stockmann, Mark; Magalhaes, Ivan L. F.; Rheims, Cristina A. (Zootaxa, 2022)
New taxonomic considerations in the spitting spider family Scytodidae Blackwall, 1864 are proposed. Here, the family is considered to include two subfamilies: Scytodinae Blackwall, 1864, comprising the genera Scytodes Latreille, 1804 and Dictis L. Koch, 1872, and Scyloxinae subfam. n., comprising the genera Scyloxes Dunin, 1992 and Stedocys Ono, 1995. Scytodes arwa Rheims, Brescovit & van Harten, 2006 is considered a senior synonym of Scytodes makeda Rheims, Brescovit & van Harten, 2006 syn. n. and the male of Scytodes kumonga Zamani & Marusik, 2020 is described for the first time, with the species being newly recorded from Oman. Observations on the natural history of S. kumonga were made using specimens raised to maturity from egg-sacs produced by females collected in Oman. The monotypic genus Soeuria Saaristo, 1997 is synonymized with Dictis, hence the transfer of its type species, D. soeur (Saaristo, 1997) comb. n. to this genus. Dictis thailandica Dankittipakul & Singtripop, 2010 is considered incertae sedis, and Dictis striatipes L. Koch, 1872 is considered a senior synonym of Dictis lugubris Thorell, 1887 syn. n., Scytodes bilqis Rheims, Brescovit & van Harten syn. n., Dictis denticulata Dankittipakul & Singtripop, 2010 syn. n., Dictis ganeshi Keswani, 2015 syn. n. and D. mumbaiensis Ahmed, Satan, Khalap & Mohan, 2015 syn. n., and the species is newly reported from several countries. Scyloxes magna (Bristowe, 1952) comb. n. and Scyloxes zhaoi (Wu & Li, 2017) comb. n. are transferred to Scyloxes from Scytodes and Stedocys, respectively.